Food Sovereignty vs. the Corporate Food Regime - McMichael, Philip (Conference Papers – International Studies Association, 2006)
In the twenty-first century, the Polanyian trinity of fictitiouscommodities (land, labor and money) cannot be realised through thetwentieth-century double movement. The regulation of money is no longervested in the state per se, but in instrumentalities such as the IMF, whosetask has become a generalized imperative to reproduce (corporate) moneythrough expending labor and land across the world with decreasing regardfor their sustainability. The construction of a 'world agriculture,'deepening the instrumental use, misuse, and abandonment of natural andsocial resources, unfolds within this general imperative. This paper arguesthat the world-wide food sovereignty movement is the most direct symptom ofthis socio-ecological crisis, embodying a diversity of responsescorresponding to the re-spatialization of social and economic relations inthe corporate food regime. As an expression of the corporate food regime,it reveals both the immanent, and the historical, conditions governing thepolitics of capitalist development under the neo-liberal project. ..PAT.-Conference Proceeding
Political Science
Keywords: commercial products; economic policy; international economic assistance; international economic relations; international studies; sovereignty

The Poverty of the Global Order: Limits of the North/South Division - Mohan, Dia; McMichael, Philip (Conference Papers – International Studies Association, 2006)
Development in the global order is represented in economically reductionist, and in impoverished, terms. The latter refers to the global reproduction of material inequality through the progressive appropriation of alternative visions of development. We argue that the legitimacy of the global order, while represented in terms of 'economic progress,' depends on the progressive naturalization of its epistemological foundations. Here, solutions to the crisis of development become methods of social control through which the dominant visions of what count as viable futures are reproduced and regulated. We critique efforts to humanise development (eg, World Bank, Amartya Sen) as evidence of developmentalism's epistemological crisis. Karl Polanyi's distinction between 'formal' and 'substantive' economy allows us to transcend the reductionism of the scarcity paradigm and revalue difference as the foundation of equality. We consider examples of substantive economy, which realise equality through strategic sovereignty and representational power, in collective and individual terms. Among other such initiatives these represent practical and epistemological 'spaces of hope' for critique of the crisis of the market epistemology that infects both development studies and international studies. Present divisions of the world must be understood as the impoverished outcomes of a market epistemology's construction and development of inequality. ..PAT.-Conference Proceeding
Political Science; International Studies
Keywords: economic development; international organization; international relations; reductionism; social control